P-85 How the west midlands cares about and prioritises research. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Coop, Hazel; Macfarlane, Michael; Twigger, Sharon; Doré, Matthew; Shayler, Stephanie; Marlow, Clare; Prew, Sandra; Willis, Derek
Abstract : Background: There is a recognised paucity of research in palliative care, compared to other specialties (Neuberger et al., 2013; Higginson, 2016). Research is key for speciality development and palliative medicine training, however, the West Midlands palliative medicine speciality registrar group identified difficulties in participating in research. Collaborative approaches to research are a beneficial way of improving quantity and quality of research (Payne et al., 2011). To address the issue of the paucity of high quality research in the region we initiated a trainee-led research collaborative. What We Did: West Midlands Collaborative Actioning Research in End-of-life and Supportive care (WM CARES) was founded in 2016. Our mission is to conduct high quality palliative care research within the region which will ultimately influence and improve patient care and services, whilst facilitating trainee participation in research. Collaboration is central to WM CARES. We are working with partners, including the National Institute for Health Research, local universities, the palliative medicine consultant body, specialty doctors and local providers of palliative care. The WM CARES network enables larger, multi-site, high quality research which crosses the boundaries of any individual registrar's placement. WM CARES has already developed four research questions into working groups under consultant supervision. Three poster presentations of our initial output have been exhibited nationally and regionally. Building on its success, WM CARES has launched a best practice event: 'WM CARES Presentations in Research, Innovation, Development and Excellence' (PRIDE). This will enable members of the multidisciplinary team to present their research and local innovative work, which will facilitate further collaboration and identify future research questions. Conclusion: WM CARES is an innovative and collaborative trainee-led research network producing high-quality research and raising the profile of research. It enables and enthuses palliative medicine specialty registrars and the wider multidisciplinary team to learn about and be involved in research activities, which will ultimately improve patient care.